Feeling Heard: Experiences of Listening (or Not) at Work - Kriz, Tiffany D.; Kluger, Avraham N.; Lyddy, Christopher J. (Frontiers in Psychology, 2021)
Listening has been identified as a key workplace skill, important for ensuring high-quality communication, building relationships, and motivating employees. However, recent research has increasingly suggested that speaker perceptions of good listening do not necessarily align with researcher or listener conceptions of good listening. While many of the benefits of workplace listening rely on employees feeling heard, little is known about what constitutes this subjective perception. To better understand what leaves employees feeling heard or unheard, we conducted 41 interviews with bank employees, who collectively provided 81 stories about listening interactions they had experienced at work. Whereas prior research has typically characterized listening as something that is perceived through responsive behaviors within conversation, our findings suggest conversational behaviors alone are often insufficient to distinguish between stories of feeling heard versus feeling unheard. Instead, our interviewees felt heard or unheard only when listeners met their subjective needs and expectations. Sometimes their needs and expectations could be fulfilled through conversation alone, and other times action was required. Notably, what would be categorized objectively as good listening during an initial conversation could be later counteracted by a failure to follow-through in ways expected by the speaker. In concert, these findings contribute to both theory and practice by clarifying how listening behaviors take on meaning from the speakers’ perspective and the circumstances under which action is integral to feeling heard. Moreover, they point toward the various ways listeners can engage to help speakers feel heard in critical conversations.